PERANCANGAN SISTEM INFORMASI PENDAFTARAN PASIEN RAWAT JALAN DAN RAWAT INAP BERBASIS LAN (LOCAL AREA NETWORK) PADA RSUD I LAGALIGO KABUPATEN LUWU TIMUR - Sri Kurniyan Sari (STMIK KHARISMA Makassar, 2018)
This study aims to design and make a patient registration information system using a website with the PHP and MySQL programming languages ​​and implement the workings of the FIFO algorithm in the program code. The type of research used is descriptive qualitative research, while the data collection method I use is interview and document collection. In the Designation of Outpatient and Inpatient Patient Registration Information Systems at the Hospital, the author implements the FIFO Algorithm (First in first out), so that it is expected that the existing problems can be resolved with information when the patient's schedule or turn time corresponds to the registration number so that the patient can estimate the time come without having to wait long. From the results of research conducted at RSUD I Lagaligo, it can be concluded that the Patient Registration Information System that has been designed and built can work as expected. The conclusions of the research results are as follows: (1) With this patient registration information system, it can facilitate the process of recording patient registration data until the doctor's examination. (2) This patient registration information system can produce output as desired. (3) Can facilitate the recording and recording of patient medical record data.